2002
DOI: 10.1152/ajpheart.00165.2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hemodynamic conditions on fractional flow reserve: parametric analysis of underlying model

Abstract: Pressure-based fractional flow reserve (FFR) is used clinically to evaluate the functional severity of a coronary stenosis, by predicting relative maximal coronary flow (Q(s)/Q(n)). It is considered to be independent of hemodynamic conditions, which seems unlikely because stenosis resistance is flow dependent. Using a resistive model of an epicardial stenosis (0-80% diameter reduction) in series with the coronary microcirculation at maximal vasodilation, we evaluated FFR for changes in coronary microvascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 49 publications
11
63
0
Order By: Relevance
“…From Fig. 9A, it can be seen that FFR cannot delineate between ES and MVD, a conclusion similar to previous studies (17,18,20,28,29,38,41). However, the other two parameters, CDP (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From Fig. 9A, it can be seen that FFR cannot delineate between ES and MVD, a conclusion similar to previous studies (17,18,20,28,29,38,41). However, the other two parameters, CDP (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…hyperemic stenosis resistance is defined as the ratio of hyperemic mean transstenotic DP to the distal average peak velocity (APV). All the three parameters fail to delineate between the ES and the MVD conditions (17,18,28,29,38,41). In addition, in the presence of MVD, an increase in microvascular resistance at downstream myocardium leads to reduction of flow and CFR values in the upstream epicardial arteries.…”
mentioning
confidence: 96%
“…18 Indeed, the original animal data showing the pressure independence of FFR has been reviewed using a Bland-Altman analysis, 19 demonstrating there can be a difference between pressure-based FFR and true flow-based FFR (Figure 2). …”
Section: Outcomes Of Ffr-guided Revascularizationmentioning
confidence: 99%
“…FFR has previously been shown to be a reliable technique to functionally assess a given coronary intermediate stenosis with unclear hemodynamic significance (1,5). A previous report has suggested that coronary outflow pressure-corrected FFR cannot only be considered a specific index for the epicardial stenosis alone (32). FFR is also a function of myocardial bed resistance, which varies as a consequence of variable hemodynamic conditions (32).…”
Section: H404 Assessment Of Coronary Microcirculation In a Swine Modelmentioning
confidence: 99%
“…A previous report has suggested that coronary outflow pressure-corrected FFR cannot only be considered a specific index for the epicardial stenosis alone (32). FFR is also a function of myocardial bed resistance, which varies as a consequence of variable hemodynamic conditions (32). Therefore, FFR cannot be used as an independent index to assess microcirculation, since it is highly affected by the presence of an epicardial stenosis.…”
Section: H404 Assessment Of Coronary Microcirculation In a Swine Modelmentioning
confidence: 99%